DUKUNGAN KELUARGA DENGAN KEMANDIRIAN ORANG DENGAN GANGGUAN JIWA (ODGJ) - Khamida Khamida; Abdul Muhith; Rizkya Dewi Safitri (Fakultas Ilmu Kesehatan, 2018)
Some families who treat people with mental disorders have fully support their family member, but people with mental disorders do not care about it. ODGJ (People with Mental Disorder) prefer to do what they want to do unless there is an award from the family. The aim of the study is to find out the relationship between family support and the level of independence of ODGJ in Posyandu Jiwa, Wonokromo Village, Surabaya. The design of this study is analytical with a cross sectional approach. The population is all ODGJ families. The sample is 35 respondents with Purposive Sampling techniques. The independent variable is family support and the dependent variable is the level of independence of ODGJ. The research instrument used a questionnaire. Data analysis using Rank Spearman test. The results showed that of the 35 respondents most (62.9%) had good family support and most (65.7%) were independent. The test results of Rank Spearman statistics p = 0.000 <α = 0.05 indicate that there is a family support relationship with the level of independence of ODGJ. The independence of ODGJ can be achieved to the maximum with good support from the family. It is expected that families can maintain good family support for ODGJ to be more independent and maintain ODGJ's independence, so as not to depend on family